Layered Video Distribution Over Integrated Services Packet Network - Yew , Chang Ching (2001)
Heterogeneity poses optimisation problems for real time video broadcast in an internet work with Internet as a prominent example. A common approach to network heterogeity is encoding of video in prioritised layers to be distributed in multiple multicast groups. In this paper , we study quality of service of QoS support for layer encoded video transport in Integrated Services network.